2011
DOI: 10.3390/ijms12117569
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine Protects INS-1 β-Cell from High Glucose-Induced ER Stress and Apoptosis

Abstract: Sustained high concentration of glucose has been verified toxic to β-cells. Glucose augments Ca2+-stimulated insulin release in pancreatic β-cells, but chronic high concentration of glucose could induce a sustained level of Ca2+ in β-cells, which leads to cell apoptosis. However, the mechanism of high glucose-induced β-cell apoptosis remains unclear. In this study, we use a calcium channel blocker, nifedipine, to investigate whether the inhibition of intracellular Ca2+ concentration could protect β-cells from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 55 publications
8
32
3
Order By: Relevance
“…[39][40][41][42] Execution of apoptosis was evident from a slight increase in caspase 3/7 activity after 72 h exposure which has also been observed in hyperglycemia treated INS-1 cells and isolated human islets. 43,44 In conclusion, this study has demonstrated multiple effects of glucotoxicity on gene expression and insulin secretory function in 1.1B4 cells, suggesting that this novel human-derived pancreatic β-cell line is useful for further investigations of β-cell dysfunction and its correction with novel therapeutic agents. …”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42] Execution of apoptosis was evident from a slight increase in caspase 3/7 activity after 72 h exposure which has also been observed in hyperglycemia treated INS-1 cells and isolated human islets. 43,44 In conclusion, this study has demonstrated multiple effects of glucotoxicity on gene expression and insulin secretory function in 1.1B4 cells, suggesting that this novel human-derived pancreatic β-cell line is useful for further investigations of β-cell dysfunction and its correction with novel therapeutic agents. …”
Section: Discussionmentioning
confidence: 99%
“…I NaL is linked to Ca 2+ homeostasis, which may thus be chronically perturbed by CHG-induced I NaL enhancement. Whereas acute increment of [Ca 2+ ] I is expected to stimulate insulin secretion [14], the only previous information on the effect of persistently elevated [Ca 2+ ] I levels concerned prevention of CHG-induced apoptosis by nifedipine [45]. The observation that RAN prevented β-cell loss in mice with streptozotocin-induced diabetes [32] is in line with this observation and conceptually reminiscent of myocardial response to persistent I NaL enhancement, i.e., transient increase in contractility followed by maladaptive remodeling [49].…”
Section: Effect Of Ran and Ttx On Membrane Potentialmentioning
confidence: 99%
“…Nevertheless, as in other tissues, pathophysiological significance of I NaL may require its enhancement under clinically relevant conditions [4,40], which in diabetes may be represented by chronic cell exposure to high glucose [45]. Thus, INS-1E cells incubated for 24 h in a medium containing 33 mM glucose (CHG) [45] were compared to cells incubated for the same period in 10 mM glucose (CNG) (Fig.…”
Section: Na -Dependent Modulation Of Intracellular Ca 2+mentioning
confidence: 99%
See 1 more Smart Citation
“…49 Damaged mitochondria release cytochrome C and induce apoptosis via the activation of caspase 9 77 ; rs2020902 is located in the CASP9 gene. 49 Sustained demands on the endoplasmic reticulum (ER) during hyperglycemia result in cytoplasmic accumulation of calcium, 86,87 causing activation of the caspase cascade 86 and 57 regulates hepatic gluconeogenesis in mice 58 Where there is more than one candidate, the gene in closest proximity to the SNP was chosen (underlined). 48 In b cells, ER stress upregulates heat shock protein 40 expression; this correlates with increased apoptosis.…”
Section: Discussionmentioning
confidence: 99%